2016
DOI: 10.1177/1744806916636386
|View full text |Cite
|
Sign up to set email alerts
|

Dietary linoleic acid-induced alterations in pro- and anti-nociceptive lipid autacoids

Abstract: BackgroundChronic idiopathic pain syndromes are major causes of personal suffering, disability, and societal expense. Dietary n-6 linoleic acid has increased markedly in modern industrialized populations over the past century. These high amounts of linoleic acid could hypothetically predispose to physical pain by increasing the production of pro-nociceptive linoleic acid-derived lipid autacoids and by interfering with the production of anti-nociceptive lipid autacoids derived from n-3 fatty acids. Here, we use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
54
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 51 publications
2
54
0
Order By: Relevance
“…We previously demonstrated in rats (11) that increasing dietary linoleic acid markedly increased the abundance of linoleic acid and its oxidized derivatives [for example, hydroxyoctadecadienoates (HODEs)] in tissues associated with idiopathic pain syndromes, including the skin. Moreover, in a trial involving 67 patients with chronic headaches, a linoleic acid–lowering dietary intervention decreased headache pain (12), and decreases in circulating linoleic acid were associated with clinical pain reduction (27), suggesting that linoleic acid or its derivatives could potentially contribute to pain in humans.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We previously demonstrated in rats (11) that increasing dietary linoleic acid markedly increased the abundance of linoleic acid and its oxidized derivatives [for example, hydroxyoctadecadienoates (HODEs)] in tissues associated with idiopathic pain syndromes, including the skin. Moreover, in a trial involving 67 patients with chronic headaches, a linoleic acid–lowering dietary intervention decreased headache pain (12), and decreases in circulating linoleic acid were associated with clinical pain reduction (27), suggesting that linoleic acid or its derivatives could potentially contribute to pain in humans.…”
Section: Discussionmentioning
confidence: 99%
“…We have previously shown in rats that increasing dietary linoleic acid increases linoleic acid derivatives in a dose-dependent manner in many tissues including the skin (11). A small human trial has found correlations between a low–linoleic acid diet intervention and decreased headache pain (12, 13) and between reductions in circulating linoleic acid and pain relief, suggesting that linoleic acid–derived mediators might contribute to sensory signaling.…”
Section: Introductionmentioning
confidence: 99%
“…A recent meta-analysis reported that fried food consumption was associated with hypertension and weight gain 50 . In vivo, the concentration of circulating oxylipins depends on the availability of their precursor fatty acid 10, 11, 51 . However, studies have demonstrated that dietary oxylipins are absorbed 1720 and incorporated into blood chylomicrons 52 .…”
Section: Discussionmentioning
confidence: 99%
“…The low LA diet contained 85.5 % saturated fatty acids, 7.4 % monounsaturated fatty acids, 2.3 % LA, and 4.8 % α-LNA [28] derived from hydrogenated coconut oil (8.73 g/100 g), flaxseed oil (0.77 g/100 g), and olive oil (0.5 g/100 g) [28]. The percent energy provided by LAwas 5.2 % en for the adequate LA diet and 0.4 % en for the low LA diet [36]. …”
Section: Methodsmentioning
confidence: 99%
“…at 250 ng/h), in view of the reported dampening effects of n-6 PUFA deprivation on brain AA metabolism [29, 31]. Rats were fed an adequate LA diet containing 27.6 % LA of total fatty acids (equivalent to 5.2 % energy (en)) or a low LA diet containing 2.3 % LA of total fatty acids (0.4 % en) [36] for 15 weeks, and then infused with LPS (250 ng/h) i.c.v. into the fourth ventricle for 2 days using a mini-osmotic pump.…”
Section: Introductionmentioning
confidence: 99%